Combining faecal calprotectin and sigmoidoscopy can predict mucosal healing in paediatric ulcerative colitis. Issue 1 (January 2020) - Kim, Seung; Park, Sowon; Kang, Yunkoo; Koh, Hong
Abstract : Objectives: Mucosal healing is the endoscopic treatment target in inflammatory bowel disease. The treat-to-target strategy, emphasizing proactive assessment and optimizing treatment, is commonly applied in the clinical setting. Although colonoscopies are essential for this strategy to be successful, bowel preparation and sedative drugs are required for paediatric patients. We attempted to verify the usefulness of sigmoidoscopy, which is less invasive than colonoscopy, combined with faecal calprotectin, to assess mucosal healing. Methods: A total of 58 paediatric patients diagnosed with ulcerative colitis and followed up at Severance Children's Hospital from March 2015 to May 2018 were enrolled. Clinical data and laboratory findings (including faecal calprotectin and endoscopic data) were collected from medical records. The predictive power of mucosal healing of sigmoid colon and rectum (s-MH) combined with faecal calprotectin to predict mucosal healing throughout the colon was analysed. Results: Among 58 patients (mean age 16.13 ± 2.88 years), 18 (31.0%) were in mucosal healing status. The median faecal calprotectin level was 486.5 μg/g. The faecal calprotectin cutoff value for predicting mucosal healing, identified using receiver-operating characteristic analyses, was 148 μg/g (area under the curve, 0.81). Sensitivity, specificity, positive predictive value, and negative predictive value of s-MH in predicting mucosal healing were 1.0, 0.82, 0.72, and 1.0, respectively. When we combined s-MH with faecal calprotectin less than the cutoff value, the sensitivity, specificity, positive predictive value, and negative predictive value were 0.56, 1.0, 1.0, and 0.83, respectively. Conclusion: For patients with a low faecal calprotectin level, sigmoidoscopy might be sufficient to assess mucosal healing. Abstract : Supplemental Digital Content is available in the text.